Evaluating the Damage Cost of Vehicle to Grid Integration in Indonesia Power Grid for Sustainable Energy System - Priyo Adi Sesotyo (International Journal of Engineering Continuity, 2025)
The cost incurred in the EV Charging is currently only from the energy consumed consideration. While there is extensive research on the impact of EV charging on grid infrastructure and operation, few studies quantify these effects in terms of explicit 'damage costs'. However, besides energy problems, the analysis of the environmental impact of EVs has not been quantified monetarily. This paper aimed to investigate the damage cost (DC) of EVs in comparison with Battery Electric Vehicles (BEVs) and Plug-in Hybrid Electric Vehicles (PHEVs) based on Indonesia Java Bali's grid conditions. Using the existing data in Indonesia, the characterisation parameter were determined using cradle-to-gate life cycle analysis (LCA) and ReCiPe 2016 then converting the endpoint indicators impacts to DC using a monetary weight factor (MWF) of those two EVs. Cradle to gate LCA is a method for evaluating the environmental impact of battery from the extraction of raw material to the factory gate and ReCiPe 2016 is a widely used of LCA method, which converts emission and resources extraction into certain indicators. Results show that DC for a 20 kWh BEV = 0.12 ± 0.01 USD/kWh compared to an 8 kWh PHEV = 0.08 ± 0.005 USD/kWh. Therefore, the DC of an extra 0.02 USD/kWh for BEVs and 0.015 USD/kWh for PHEVs should be considered in formulating the EV charging tariff.